Journal of Cheminformatics - Willighagen, Egon.; Guha, Rajarshi; Zdrazil, Barbara; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: BioMed Central.)
Journal of Cheminformatics is an open access journal publishing original peer-reviewed research in all aspects of cheminformatics. Coverage includes, but is not limited to: chemical information systems, software and databases, and method development for molecular modelling chemical structure representations and their use in structure, substructure, and similarity searching of chemical substance and chemical reaction databases computer and molecular graphics, computer-aided molecular design, expert systems, QSAR, and data mining techniques.
Keywords: Chemoinformatics; Chemistry$1 (BData processing.s; Chemistry, Physical and theoretical; Bioinformatics; Cheminformatics; Computational Chemistry; Theoretical Chemistry; Bioinformatics